2012
DOI: 10.1115/1.4023132
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Aortic Flow Stability and Comparison With In Vivo Flow Measurements

Abstract: The development of an engineering transitional turbulence model and its subsequent evaluation and validation for some diseased cardiovascular flows have been suggestive of its likely utility in normal aortas. The existence of experimental data from human aortas, acquired in the early 1970s with catheter-mounted hot film velocimeters, provided the opportunity to compare the performance of the model on such flows. A generic human aorta, derived from magnetic resonance anatomical and velocity images of a young vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
2
33
0
3
Order By: Relevance
“…Salsac et al (2006) also provides a thorough description of the unsteady wall shear stress, but does not consider the instability and laminar-turbulent transition of the vortex ring. Both studies from Peattie et al (2004) and Salsac et al (2006) investigate peak Reynolds numbers based on the undilated vessel diameter of Re = 2300 and Re = 2700 , which is presumed to be too low for the human aorta (Kousera et al 2013). Yip andYu (2001, 2003) provide an overall description of the flow inside an aneurysm, and discuss the stability and decay of the vortex, as well as the spatial and temporal evolution of the WSS.…”
Section: Introductionmentioning
confidence: 99%
“…Salsac et al (2006) also provides a thorough description of the unsteady wall shear stress, but does not consider the instability and laminar-turbulent transition of the vortex ring. Both studies from Peattie et al (2004) and Salsac et al (2006) investigate peak Reynolds numbers based on the undilated vessel diameter of Re = 2300 and Re = 2700 , which is presumed to be too low for the human aorta (Kousera et al 2013). Yip andYu (2001, 2003) provide an overall description of the flow inside an aneurysm, and discuss the stability and decay of the vortex, as well as the spatial and temporal evolution of the WSS.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to consider the turbulent flow behaviour can cause a large numerical error. Kousera et al reported stability of aortic flow [8]. Using the Reynolds-averaged Navier–Stokes-based shear stress transport transitional model to compute various Reynolds numbers ranging from 4000 to 10,000 and Womersley parameters ranging from 17 to 26, they concluded that the model is capable of capturing the correct flow state by comparing the results to experimentally acquired in vivo flow measurements using a catheter-mounted hot-film probe.…”
Section: Introductionmentioning
confidence: 99%
“…Altered hemodynamics is associated with aorta pathologies (aneurysms and stenosis) affecting the long-term outcome of patients (1,3,12). The accuracy of CFD results is, however, mainly affected by a choice of the appropriate CFD model, as shown in a set of numerical studies (13)(14)(15)(16)(17). In this proof-of-concept study we compared MRIbased CFD with catheter-derived peak systolic pressure drops in a clinical setting in patients with CoA.…”
mentioning
confidence: 99%